Effect of Combined Probiotics and Zinc Supplementation on Immune Status of Pulmonary Tuberculosis Patients - Setiyaningrum, Zulia; Darmono, S.S.; Sofro, Muchlis Achsan Udji; Dharmana, Edi; Widyastiti, Nyoman Suci (Pakistan Journal of Nutrition, 2016)
Patients with pulmonary tuberculosis generally malnourished due to side effect in anti-tuberculosis drugs, which altering gastrointestinal tract, it affects on recovery process, immune system and response. Probiotics and zinc are thought to have beneficial effects for nutritional status and immune response. This study was conducted to analyze the effect of combined probiotics and zinc on levels of lymphocytes, neutrophils lymphocyte count ratio (NLR) and monocytes in patients with pulmonary tuberculosis in Lung Health Center of Semarang. In a quasi-experimental study (quasi experiment) randomized design with pre-post test control group design, fifty four pulmonary tuberculosis patients were divided into 2 groups, the treatment group received a combination of probiotics and zinc, as well as a control group given a placebo, administration for 4 weeks. There were no differences in mean age, levels of lymphocytes and monocytes NLR at baseline (p>0.05). Increased levels of lymphocytes and decreased levels of monocytes and NLR after administration of the combination of probiotics and zinc (p0.05). The most powerful effectiveness of the combination probiotics and zinc contained in the lymphocyte levels (12.8%). It is concluded that the combined probiotics and zinc over 4 weeks improve the immune system of patients with pulmonary tuberculosis measured by lymphocytes, NLR and monocytes.